The Effect Of Partial Shading On Photovoltaic Panel Performance - Idnan, Muhammad Amirul Husni (Universiti Sains Malaysia, 2017)
Shading gives a great effect in the power output of the Photovoltaic panel. Shading can be divided into two type, uniform and non-uniformly distributed. Uniform shading created by using butter paper where all the area of solar panel cover by shading. Non-uniform shading created by using leaves and trees where the partial area of solar panel cover by shading. The performance of solar panel will be analyzed using measuring sensors. The performance of solar panel is being analyzed based on two main conditions. First uniform shading with series and parallel connection of solar panel. Second, non-uniform shading with series and parallel connection of solar panel. Firstly, solar panel testing is conducted with uniform shading with a series connection to observe I-V characteristic. Then, the connection change to parallel and the I-V characteristic was observed. Secondly, the same method which has been used for non-uniform shading. A number of performance parameters have been collected using Arduino Mega over 5 hours per a day for each condition. Based on results obtained, it shows that having 10 to 11% of shading will decrease the performance of the solar panel. The increasing percentage of shading will decrease the performance of the solar panel. In practical, the effect on uniform shading like dust will not give a great effect like butter paper.